Combining Unique Planar Biaxial Testing with Full‐Field Thickness and Displacement Measurement for Spatial Characterization of Soft Tissues. Issue 7 (18th July 2022) - Pearce, Daniel; Nemcek, Mark; Witzenburg, Colleen
Abstract: Soft tissues rely on the incredible complexity of their microstructure for proper function. Local variations in material properties arise as tissues develop and adapt, often in response to changes in loading. A barrier to investigating the heterogeneous nature of soft tissues is the difficulty of developing experimental protocols and analysis tools that can accurately capture spatial variations in mechanical behavior. In this article, we detail protocols enabling mechanical characterizations of anisotropic, heterogeneous soft tissues or tissue analogs. We present a series of mechanical tests designed to maximize inhomogeneous strain fields and in‐plane shear forces. A customized, 3D‐printable gripping system reduces tissue handling and enhances shear. High‐resolution imaging and laser micrometry capture full‐field displacement and thickness, respectively. As the equipment necessary to conduct these protocols is commercially available, the experimental methods presented offer an accessible route toward addressing heterogeneity. © 2022 The Authors. Current Protocols published by Wiley Periodicals LLC. Basic Protocol 1 : Unique biaxial testing of soft tissues and tissue analogs Basic Protocol 2 : Full‐field thickness measurement of soft tissues and tissue analogs Support Protocol 1 : Creating and speckling cruciform‐shaped samples for mechanical testing Support Protocol 2 : Creating custom gripping system to minimize sample handling